2015
DOI: 10.1007/s13224-015-0673-1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Incomplete Abortion Following Medical Method of Abortion (MMA)

Abstract: Background Medical method of abortion (MMA) is a safe, efficient, and affordable method of abortion. However, incomplete abortion is a known side effect. Objective To study incomplete abortion due to medication abortion and compare to spontaneous incomplete abortion and to study referral practices and prescriptions in cases of incomplete abortion following MMA. Method Prospective observational study of 100 women with first trimester incomplete abortion, divided into two groups (spontaneous or following MMA), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…In study of Pawde 63% of women taking MMA required BT but in study of Henderson, they found that though heavy bleeding was common, severe bleeding requiring blood transfusion was low. 4,8 In my study however, blood transfusion was required in 60% patients with average haemoglobin (Hb) 4-6 gm%.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In study of Pawde 63% of women taking MMA required BT but in study of Henderson, they found that though heavy bleeding was common, severe bleeding requiring blood transfusion was low. 4,8 In my study however, blood transfusion was required in 60% patients with average haemoglobin (Hb) 4-6 gm%.…”
Section: Discussionmentioning
confidence: 77%
“…As compared to 21.8% of Pawde et al, in my study majority of patients took the medicine over the counter or advised by quacks (88%). 4 In my study only 12% women obtained medication from MBBS doctors. Rest was either suggested by local unauthorized practitioners or over the counter self-administration.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, accessing misoprostol does not necessarily guarantee safe abortion if the modalities of it uses are not respected. Improper use of misoprostol can lead to life-threatening complications such as collapse, bleeding and fever [11]. Moreover, a recent report on the issue of abortion worldwide suggests that clandestine abortion in legally restrictive settings is becoming relatively safer as misoprostol is replacing harmful methods [12].…”
Section: Introductionmentioning
confidence: 99%
“…5 Other than consumption of MA drugs, incomplete abortion can occur due to spontaneous abortion, miscarriage, prolonged or abnormal bleeding, infection of the uterus, intra uterine fetal death (IUD) etc. 6,7 Incomplete abortion contributes significantly to mortality and morbidity, affecting subsequent fertility and causing psychological distress. 8 Abortions, be it spontaneous or induced, are most common adverse outcome of pregnancy.…”
mentioning
confidence: 99%